THE EFFECT OF COMBINED ANTIHYPERTENSIVE THERAPY ON THE BASIC PARAMETERS OF THE LEFT VENTRICLE MYOCARDIUM STRUCTURE AND FUNCTION IN WOMEN WITH METABOLIC SYNDROME AND HYPOTHYROIDISM - V. V. Skibitskiy; A. V. Fendrikova; N. E. Pykhalova (Столичная издательская компания, 2015)
Aim. To study the effect of combined antihypertensive therapy on the basic parameters of the left ventricle (LV) myocardium structure and function in women with arterial hypertension (HT), metabolic syndrome (MS) and hypothyroidism. Material and methods. Women (n=196) with HT grade 2-3 and MS were included into the study. Standard clinical examination including an assessment of thyroid status, ambulatory blood pressure (BP) monitoring and echocardiography was performed at baseline and after 6 months. The patients were split into 3 groups: control (without hypothyroidism) with subclinical and manifested (symptomatic) hypothyroidism (SH and MH). Depending on baseline heart rate (HR) patients of each group received a combination of amlodipine+losartan (A+L) in HR <85/min or a combination of amlodipine+moxonidine (A+M) in) in HR ≥85/min. Results. The significant antihypertensive effect was found in patients of the control group due to both A+L and A+M combination (target BP was reached in 85.7 and 88.2%, respectively). In patients with hypothyroidism significant antihypertensive effects was observed only during A+M therapy (target BP in SH and MH was achieved in 82.8 and 82.4%, respectively). In the control group A+L and A+M combinations increased a number of patients with normal LV geometry (85.7 and 86.7, respectively) and diastolic function (78.6 and 80%, respectively). In hypothyroidism A+M therapy resulted in more prominent increase in a number of patients with normal LV geometry (75% in both SH and MH) and diastolic function (in SH and MH 83.3 и 85.7%, respectively) than these in A+L therapy (р<0.05). Conclusion. The combination of A+M has advantages over A+L combination in antihypertensive efficacy as well as in the effect on the structural and functional state of the LV myocardium in women with HT and MS associated with hypothyroidism.